Development of a conceptual model evaluating the humanistic and economic burden of Crohn's disease: implications for patient-reported outcomes measurement and economic evaluation. (August 2015) - Gater, Adam; Kitchen, Helen; Heron, Louise; Pollard, Catherine; Håkan-Bloch, Jonas; Højbjerre, Lise; Hansen, Brian Bekker; Strandberg-Larsen, Martin
<x xml:space="preserve">Abstract</x> The primary objective of this review is to develop a conceptual model for Crohn's disease (CD) outlining the disease burden for patients, healthcare systems and wider society, as reported in the scientific literature. A search was conducted using MEDLINE, PsycINFO, EconLit, Health Economic Evaluation Database and Centre for Reviews and Dissemination databases. Patient-reported outcome (PRO) measures widely used in CD were reviewed according to the US FDA PRO Guidance for Industry. The resulting conceptual model highlights the characterization of CD by gastrointestinal disturbances, extra-intestinal and systemic symptoms. These symptoms impact physical functioning, ability to complete daily activities, emotional wellbeing, social functioning, sexual functioning and ability to work. Gaps in conceptual coverage and evidence of reliability and validity for some PRO measures were noted. Review findings also highlight the substantial direct and indirect costs associated with CD. Evidence from the literature confirms the substantial burden of CD to patients and wider society; however, future research is still needed to further understand burden from the perspective of patients and to accurately understand the economic burden of disease. Challenges with existing PRO measures also suggest the need for future research to refine or develop new measures.